Features of implementation of the module-rating continuous control and estimation of teaching system of future managers-economists in higher education institutes on the basis of information technologies - KOVAL, Tamara (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the features of implementation of the module-rating continuous control and estimation of teaching system of future managers-economists in higher education institutes on the basis of information technologies. This system is based on the story, module, rating principles of the readiness to professional computer activity evaluation and on the realization of fi nal and inter-session types of preparation effi ciency control.